Transforming Correspondence Learning Through Microlearning-Based Media for Vocational High School Students - Marsofiyati; Eryanto, Henry; Faslah, Roni; Swaramarinda, Darma Rika; Yuliawan, Rahmat; Rasto, Rasto; Muhidin, Sambas Ali; Latief, M. Jamil; Santoso, Jarot Tri Bowo (JTP - Jurnal Teknologi Pendidikan, 2024)
The rapid development of digital technology requires innovative learning media to improve the student learning experience. This study discusses the development of microlearning-based correspondence learning media designed for Vocational High School (SMK) students under the auspices of the Indonesian Association of Scholars and Office Administration Practitioners (Aspapi) in Jakarta area. The main problem in correspondence learning is the limited effective media to increase students' focus and learning independence. Students often have difficulty in structuring sentences when writing letters and are reluctant to think deeply due to the familiarity with informal communication through social media as well as a lack of knowledge of formal correspondence. This research aims to develop microlearning-based learning media in correspondence learning. The method used is Research and Development (R&D) with the Dick & Carey development model, which includes needs analysis to summative evaluation. The respondents in this study are students of Aspapi's partner vocational schools in Jakarta. The results show that microlearning-based learning media significantly increases the effectiveness of correspondence learning. Students demonstrate better comprehension and increased learning independence thanks to concise and directed microlearning content, in accordance with their digital communication habits. Interactive and accessible media design also helps to overcome low literacy competence and student learning motivation.  Based on the above findings, it can be concluded that the development of microlearning-based learning media has proven to be an effective solution in overcoming challenges in correspondence learning. This media is able to improve students' writing skills, critical thinking, and learning independence, so similar innovations are recommended to be applied to other administrative and vocational subjects.